Angklung Art: Reflection of Mutual Cooperation Culture (Case Study on Angklung Playing and Learning at SMAN 1 Lembang, West Bandung, West Java) - Kasmahidayat, Yuliawan; Pamungkas, Rully (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2023)
The Angklung art is a unique form of Indonesian art originating from West Java. It is deeply rooted in the staple food of rice and the myth of Nyi Sri Pohaci, the Goddess Sri who gives life to the Sundanese people and helps them manage agriculture and cultivation. While Angklung music is a form of entertainment, it also teaches the value of cooperation in the community. The research approach used in this study was arts education and cultural studies, with a descriptive-analytical research method using a qualitative approach. The study shows that arts education can contribute to the development of the cultural character of cooperation in society through Angklung music. The results of the study indicate the effectiveness of arts education in reflecting the culture of cooperation in communities across various regions, particularly in the Sundanese area. It was concluded that the use of Angklung art as a learning medium has been found to be effective in reflecting a culture of cooperation as well as community characters and skills. Abstrak Kesenian angklung merupakan kesenian khas Indonesia berasal dari Jawa Barat. Seni angklung bersumber pada makanan pokok berupa padi, mitos Nyi Sri Pohaci sebagai Dewi Sri pemberi kehidupan bagi masyarakat Sunda, dalam mengelola pertanian dan perladangan. Musik Angklung selain sebagai permainan, juga sebagai pembelajaran yang mencerminkan karakter gotong royong masyarakat. Pendekatan yang digunakan dalam penelitian ini adalah pendidikan seni dan kajian budaya. Metode yang digunakan adalah metode penelitian deskriptif analitis dengan pendekatan kualitatif. Hasil penelitian berupa kontribusi pendidikan seni dalam menumbuh-kembangkan karakter budaya gotong royong pada masyarakat melalui media angklung. Hasil penelitian menunjukan efektifitas dari pendidikan seni dalam pencerminan budaya gotong royong pada masyarakat di berbagai wilayah khususnya di tatar Sunda. Disimpulkan melalui media pembelajaran dan permainan musik angklung, diperoleh efektivitas terhadap pencerminan budaya gotong royong,pengetahuan dan keterampilan pada masyarakat.